2013
DOI: 10.2215/cjn.07680712
|View full text |Cite
|
Sign up to set email alerts
|

Serum Soluble Urokinase-Type Plasminogen Activator Receptor Levels and Idiopathic FSGS in Children

Abstract: SummaryBackground and objectives FSGS is the primary cause of childhood nephrotic syndrome leading to ESRD. Permeability factors, including circulating serum soluble urokinase-type plasminogen activator receptor (suPAR), have been postulated as putative causes in adults with primary FSGS. Similar results have yet to be proven in children.Design, setting, participants, & measurements This cross-sectional single-center study assessed the association of serum suPAR in children with FSGS or other glomerular and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
73
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 29 publications
5
73
2
1
Order By: Relevance
“…Recent findings suggest that increased levels of circulating soluble urokinase-type plasminogen activator receptor (suPAR) may trigger the podocytopathy in the majority of patients with primary FSGS. In this issue, Bock et al (2) report findings in 99 pediatric patients at a single center and conclude that serum suPAR levels are not increased in those with primary FSGS compared with children with non-FSGS glomerular disease, nonglomerular disease, or healthy controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that increased levels of circulating soluble urokinase-type plasminogen activator receptor (suPAR) may trigger the podocytopathy in the majority of patients with primary FSGS. In this issue, Bock et al (2) report findings in 99 pediatric patients at a single center and conclude that serum suPAR levels are not increased in those with primary FSGS compared with children with non-FSGS glomerular disease, nonglomerular disease, or healthy controls.…”
mentioning
confidence: 99%
“…The hypothesis that circulating suPAR drives the disease in a subset of FSGS is directly challenged by Bock et al (2) in this issue of CJASN. They report that suPAR levels were not significantly different in children with primary FSGS (n520), non-FSGS glomerular disease (n5240), nonglomerular CKD (n526), and healthy controls (n529).…”
mentioning
confidence: 99%
“…18 Ancak daha yeni çalış-malar, suPAR'ın primer FSGS'de etken olduğuna dair kuşkulara yol açmıştır. 19,20 İMMÜNOLOJİK ANORMALLİK NS'nin immün sistemin disregülasyonu sonucu oluştuğuna dair teori en az 30 yıldır mevcuttur. Relaps sırasında hem humoral hem de hücresel immün yanıtlarda anormallik olduğuna dair pek çok rapor mevcuttur.…”
Section: Pri̇mer Glomerüler Defektunclassified
“…Most importantly, patients with eGFRs below 40 ml/min per 1.73 m 2 at baseline were excluded. This may have filtered out the significant effects of moderate to severe CKD on suPAR concentrations, thus obfuscating the observed reciprocal relationship between eGFR and suPAR concentrations seen in other studies (8,9). Also, the study population pools results from children and adults with FSGS.…”
mentioning
confidence: 99%
“…First, serum suPAR concentrations could not discriminate patients with primary versus secondary FSGS or patients at risk of recurrent FSGS after kidney transplantation (5-7). Second, studies looking at determinants of serum concentrations identified kidney function to be one of the most important determinants of suPAR (8,9). This argues against the use of an absolute suPAR concentration cutoff as a biomarker for underlying FSGS.…”
mentioning
confidence: 99%